Pre-treatment of wastewater at wet market using effective microorganism (EM) technology - Nur Afiqa, Ishak (2010)
Wastewater quality was very important because it surround us almost everywhere. Aquatic life can be destroyed and health problems also can occur and affect human being. The quality of wastewater coming from wet market was known to be a public problem before it being treated. Pre-treatment process by using environment friendly method, Effective Microorganism (EM) Technology was proposed to be a solution way to reduce pollution problem with the wastewater. The objectives of the research were to determine the level of parameters of wastewater coming from the wet market and to see how effectiveness of using EM technology as the pre-treatment of the wastewater from the wet market. Sample taken from Pasar Borong Kemunting, Pahang and be analyzed in UMP laboratory. The experimental was carried out once a week and continues for 12 weeks period. The 7 parameters were analyzed which include pH, Turbidity, Total Dissolve Solid (TDS), Ammonia Nitrogen, Total Suspended Solid (TSS), Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD). The 7 parameters will be referred to Standard Examination of Water and Wastewater by American Public Health Associate (APHA, 2002). In this research, wastewater sample collected from the wet market being added by two types of EM which were Effective Cultura (EC) and J-M2 1 (JM). The results obtained then being compared to the Interim National Water Quality Standard (INWQS) for Malaysia to see the differences. Statistical analysis of the data to evaluate performance differences among two type of EM was done by using Independent Sample T-test in Social Scientific Statistical Software (SPSS). Based on the finding result, it was found that most of the parameter improved in water quality after EM was added like turbidity, AN, TSS, COD and BOD. The most positively improvement from the results was turbidity parameter, which changes from Class II to nearly Class I after pre-treatment were made. Turbidity percentages of changing were determined as 73% for EC and 74.7% for JM. However, more time was needed to see the optimum reaction of the EM. From the study, it hopes to provide solutions to the pollution. EM technology was easy to use and cost effective because it does not requires changes to the existing treatment and collection system and application equipment is relatively inexpensive.